Pengembangan Sistem Informasi E-Recruitment Untuk Seleksi Penerimaan Karyawan Baru Berbasis Web - Desi Febriyani; Sri Ipnuwati; Helen Aggraini; Hilda Dwi Yunita (Jurnal Teknologi dan Informatika (JEDA), 2022)
Technological developments are increasingly rapid, companies need skilled workers so that they can bring companies to develop and compete with technological developments, aspects of employee recruitment are very influential on the progress of the company, recruitment processes that are not in accordance with company needs can hinder company development as in the process of recruiting prospective employees who have to go directly to the company address or send via post and email, this takes a lot of time, lots of piles of unused job applications and creates spam and takes a long time to sort through. Based on this, the researcher proposes an e-Recruitment Information system innovation to assist the recruitment process, including the process of inputting and searching for new employee recruitment data. The research design resulted in a software engineering of Employee E-Recruitment Information systems at PT. XYZ which makes it easier for the human resources department to accept new employees. In addition, the Employee E-Recruitment Information System at PT. The new XYZ can speed up the time in the process of recruiting, inputting and searching for new employee candidate data.